2022
DOI: 10.1097/corr.0000000000002131
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Interrater and Intrarater Reliability of the Lawrence and Botte Classification System of Fifth Metatarsal Base Fractures?

Abstract: Background Fractures of the proximal fifth metatarsal are common, and often they are classified using a three-part scale first proposed by Lawrence and Botte. A clear consensus on prognosis and treatment for these fractures is lacking, particularly for fractures in the middle classification, Zone 2; the reliability of the classification scheme itself may be partly at fault for this. The intra-and interrater reliability of the classification itself has never been established, and it remains unclear whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The authors of this study [6] nicely show that simplifying the Lawrence and Botte classification from three zones to two zones markedly increased the interrater and intrarater reliability. Likewise, Morris et al [5] presented biomechanical data that revealed a distinctive change in stability between proximal fifth metatarsal fractures that were within the peroneal brevis insertional footprint (Lawrence and Botte Zone 1) compared with those proximal to the footprint (Lawrence and Botte Zones 2 and 3).…”
Section: How Do We Get There?mentioning
confidence: 83%
See 4 more Smart Citations
“…The authors of this study [6] nicely show that simplifying the Lawrence and Botte classification from three zones to two zones markedly increased the interrater and intrarater reliability. Likewise, Morris et al [5] presented biomechanical data that revealed a distinctive change in stability between proximal fifth metatarsal fractures that were within the peroneal brevis insertional footprint (Lawrence and Botte Zone 1) compared with those proximal to the footprint (Lawrence and Botte Zones 2 and 3).…”
Section: How Do We Get There?mentioning
confidence: 83%
“…In the current study, Noori et al [6] appropriately challenged the validity and reliability of the commonly used Lawrence and Botte classification system for the treatment and prognosis of fifth metatarsal base fractures. They found that the Lawrence and Botte classification system demonstrated low interrater and intrarater reliability, even among surgeons specializing in foot and ankle surgery.…”
Section: Where Are We Now?mentioning
confidence: 92%
See 3 more Smart Citations